2016
DOI: 10.1159/000446198
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Intake and Vasopressin: Connecting the Dots

Abstract: In the last decade, cross-sectional and multiple cohort studies have associated total fluid intake or water intake with the risk for chronic kidney disease (CKD) and even the risk of developing hyperglycemia. Urine biomarkers have also been linked to the risk of CKD and lithiasis, and these biomarkers respond quickly to variations in fluid intake. High circulating copeptin levels, a surrogate marker of arginine vasopressin, have been associated with metabolic syndrome, renal dysfunction and increased risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…The impact of low daily water intake on long term health has, in the past, attracted little attention [10]. A recent study revealed, however, that plasma vasopressin (ADH) levels were significantly enhanced in low drinkers (≤ 1.2 litres/d of total fluid intake, i.e.…”
Section: Impact Of Drinking Behaviour On the Vasopressin-cortisol-sgkmentioning
confidence: 99%
“…The impact of low daily water intake on long term health has, in the past, attracted little attention [10]. A recent study revealed, however, that plasma vasopressin (ADH) levels were significantly enhanced in low drinkers (≤ 1.2 litres/d of total fluid intake, i.e.…”
Section: Impact Of Drinking Behaviour On the Vasopressin-cortisol-sgkmentioning
confidence: 99%
“…Plasma concentration of AVP has been classically used in the diagnostic process of all these disorders, but its structural instability, its very short plasma half-life and, last but not least, the long-lasting laboratory processing have limited its use in clinical practice [6,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Low fluid intake, or its biomarkers, has been associated with an increased risk of developing cardiometabolic diseases [ 1 , 2 ], chronic kidney disease [ 3 ] and recurrent kidney stones [ 4 ]. Adequate hydration has been shown to improve cognition in children [ 5 ] and adults [ 6 ], improve mood [ 7 , 8 ] and attenuate biological risk factors for the above-mentioned conditions.…”
Section: Introductionmentioning
confidence: 99%